Can Payers Use Prices to Improve Quality? Evidence from English Hospitals. (11th November 2014) - Allen, Thomas; Fichera, Eleonora; Sutton, Matt
Abstract: In most activity‐based financing systems, payers set prices reactively based on historical averages of hospital reported costs. If hospitals respond to prices, payers might set prices proactively to affect the volume of particular treatments or clinical practice. We evaluate the effects of a unique initiative in England in which the price offered to hospitals for discharging patients on the same day as a particular procedure was increased by 24%, while the price for inpatient treatment remained unchanged. Using national hospital records for 205 784 patients admitted for the incentivised procedure and 838 369 patients admitted for a range of non‐incentivised procedures between 1 December 2007 and 31 March 2011, we consider whether this price change had the intended effect and/or produced unintended effects. We find that the price change led to an almost six percentage point increase in the daycase rate and an 11 percentage point increase in the planned daycase rate. Patients benefited from a lower proportion of procedures reverted to open surgery during a planned laparoscopic procedure and from a reduction in long stays. There was no evidence that readmission and death rates were affected. The results suggest that payers can set prices proactively to incentivise hospitals to improve quality. Copyright © 2014 John Wiley & Sons, Ltd.